Rapid evidence profile #83: Diagnosing central auditory processing disorder - Waddell, K; Grewal, E; Dass, R; Ciurea, P; Whitelaw, H; Goodale, G; Bain, T; Phelps, A; Wilson, MG (My University, 2024)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about diagnosing central auditory processing disorder in response to a decision-maker’s request.
Keywords: central; auditory; processing; disorder